Admission Decisions Made by Emergency Physicians Can Reduce the Emergency Department Length of Stay for Medical Patients - Yuri Choi; Jinwoo Jeong; Byoung-Gwon Kim (Emergency Medicine International)
Background. Emergency department (ED) overcrowding is a worldwide problem that poses a threat to patient safety by causing treatment delays and increasing mortality. Consultations are common and important in the emergency medicine profession and are associated with longer ED length of stay (LOS). The purpose of this study was to evaluate the impact of admission decisions by emergency physicians without consultations on the ED LOS and other quality indicators. Methods. The study was a retrospective observational study comparing the ED LOS of patients admitted to the internal medicine (IM) department before and after the policy change regarding admission decisions that was implemented in October 2016. During and after the policy change, emergency physicians decided how to arrange for and treat medical patients by processing their admission and providing follow-up care without consultations. The ED LOS and other indicators of patients admitted to the IM department were compared between the study period (January to June 2017) and the control period (January to June 2016). Results. The median ED LOS of patients admitted to the IM department decreased from 673 (IQR: 347–1,369) minutes in the control period to 237 (IQR: 166–364) minutes in the study period. There were no significant differences in the interdepartmental transfer rate or in-hospital mortality between the two periods. Conclusions. The admission decisions regarding medical patients made by emergency physicians without specialty consultations reduced the ED LOS without a significant negative effect on mortality or hospital LOS.